Penerapan Teknologi Pengoperasian, Perawatan dan Pelatihan Mikro Hidro di Desa. Karang Suko KecAMATAN Pagelaran KabUPATEN Malang - Muhammad Irfan; Machmud Effendy; Ali Mokhtar; Suwignyo . (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2015)
Penerapan Teknologi Pengoperasian, Perawatan danPelatihan Mikro Hidro di Desa. Karang Suko KecAMATANPagelaran KabUPATEN MalangMuhammad Irfan1, Machmud Effendy2, Ali Mokhtar3, Suwignyo4 1,2,3,4Fakultas Teknik Universitas Muhammadiyah MalangEmail : 1)Irfan_tsd@yahoo.com, 2)machmudeffendy@yahoo.com, 3)alimokhtar011@gmail.com, 4)wignyo_08@yahoo.comABSTRAKMicro hydro power plant ( MHPP ) Sumber Maron located in the village of Karangsuko, districts Pagelaran, Malang district. It has been in operation since 2011. Sustainability Mikro Hidro Power (MHP) system depends on many things , one of them is a good way of operation and proper maintenance. The main problem is the unavailability of operators who are able to overcome with disturbances and maintain of MHP system . The purpose of science and technology program activities for the community is to produce the human resources were able to operate , maintain and overcome the slight disturbance in the MHP system. Methods of science and technology program for community activities was carried out by using PRA ( Participatory Rapid Appraissal ) , which is a method that is both empowering and Bottom - up Participatory Approach , by doing workshops and practice . The material of the workshop is the introduction of the MHP system, the components of MHP, on how to operate , maintain all the resources MHP correctly , how to cope with distraction MHP, and health and safety. The results of this activity is the availability of human resources having appropriate skills standards , start from the basic principles operate , maintain and how to resolve the problem if there is interference on all the resources at MHP.Keywords: MHPP, PRA, Science and Technology